Congestion control mechanisms for convergence networks - a comparative study - Shefali Nagpal. (2008)
In this project, we focus on a comparative study for the existing mechanisms and design a modified solution. Simulated software-model have been designed and coded within the NS2 network simulation environment specifically for the purpose of providing such a comparative analysis. The traffic is generated using application models such as FPT as well as bursty transmissions across multiple users on varying link bandwidths. The resulting congestion data from these protocols is then compared and the results presented.